2020
DOI: 10.3389/fcell.2020.00668
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia Chemo-Resistance Is Mediated by E-selectin Receptor CD162 in Bone Marrow Niches

Abstract: The interactions of leukemia cells with the bone marrow (BM) microenvironment is critical for disease progression and resistance to treatment. We have recently found that the vascular adhesion molecule E-(endothelial)-selectin is a key niche component that directly mediates acute myeloid leukemia (AML) chemo-resistance, revealing E-selectin as a promising therapeutic target. To understand how E-selectin promotes AML survival, we investigated the potential receptors on AML cells involved in E-selectin-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…Especially, the role of the sialyl Lewis x/a (sLe x/a ) antigen expression in AML and its direct interaction with E-selectin in the bone marrow niche is intriguing. Reported implications of this interplay include altered homing of leukemic cells as well as regulation of their cellular proliferation and quiescence, respectively [ 17 , 18 , 19 ]. In a recent report, Barbier et al showed that the interaction between sLe x/a and E-selectin is a major determinant of chemoresistance in AML [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the role of the sialyl Lewis x/a (sLe x/a ) antigen expression in AML and its direct interaction with E-selectin in the bone marrow niche is intriguing. Reported implications of this interplay include altered homing of leukemic cells as well as regulation of their cellular proliferation and quiescence, respectively [ 17 , 18 , 19 ]. In a recent report, Barbier et al showed that the interaction between sLe x/a and E-selectin is a major determinant of chemoresistance in AML [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR-Cas9 gene editing technology also helped to estabilish that P-selectin (CD162), but not CD44, is involved in E-selectin-mediated chemo-resistance in vitro. The onset of AML occurs later when DC162 is absent from the cell surface, and sensitivity to in vivo chemotherapy is higher 35 .…”
Section: Therapeutic Resistancementioning
confidence: 99%
“…Very recently, the membrane E-selectin receptor expressed on HSCs and responsible for induction of chemoresistance was identified [48] . E-selectin may interact with two different membrane receptors, CD44 and CD162, expressed on hematopoietic cells.…”
Section: Targeting Leukemic Endotheliummentioning
confidence: 99%
“…Only the silencing of both receptors abrogates the capacity of KG1a cells to bind E-selectin; however, only CD162 is critical for E-selectin-mediated chemoresistance in vitro. Importantly, CD162 expression on AML cells in vivo is a major determinant for E-selectin binding, bone marrow vascular niche retention, and leukemic progression [48] [Figure 2]. Deletion of CD162 in AML cells induces a clear increase of the sensitivity of leukemia stem cells to therapy [48] .…”
Section: Targeting Leukemic Endotheliummentioning
confidence: 99%
See 1 more Smart Citation